2019
DOI: 10.3390/electronics8091030
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Microwave Planar Sensor for Dielectric Assessment of Vegetable Oils

Abstract: We report on the numerical simulations and experimental validation of a microwave planar sensor based on two coupled rings operating in the 4-6 GHz range. The fabricated sensor is used to characterize the dielectric permittivity of vegetable oils. We optimized the geometrical parameters in order to improve the overlap between the oil samples under study and the electric field. The experimental results showed an excellent match with the simulation results. The fabricated sensor allowed to retrieve the oil permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Both S and FoM values are still inferior than others reported so far for several olive oil sensors. However, the resonance frequency shift is in perfect agreement with spectroscopic evidence. As previously discussed, Raman spectrum for VOO shows two distinct peaks at 1515 and 1152 cm –1 , which are not presented in spectra of other oil types (Supporting Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both S and FoM values are still inferior than others reported so far for several olive oil sensors. However, the resonance frequency shift is in perfect agreement with spectroscopic evidence. As previously discussed, Raman spectrum for VOO shows two distinct peaks at 1515 and 1152 cm –1 , which are not presented in spectra of other oil types (Supporting Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…The analogy in the response between SRRs and CSRRs is described by the Babinet principle . Regarding oil quality sensing, several metasurface structures have been proposed, exhibiting good sensing capabilities. Nonetheless, none of them are complementary. Consequently, CSRRs could be investigated as alternative options for oil quality control.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [ 24 ], it was shown that planar sensors could be used to assess the composition of vegetable oils, and in ref. [ 25 ], the authors demonstrated that food pathogens could be detected through variation in dielectric properties via impedance sensors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, with the development of 5G technology, the accurate characterization of substrate parameters, especially at millimeter and terahertz frequencies, is highly important [3][4][5]. Permittivity measurement is also playing an increasingly important role in agriculture, the food industry, material science, and biomedical engineering in the last few years [6][7][8][9], due to its obvious advantages of being direct, label-free, sensitive, nondestructive, etc. One emerging application is the real-time detection and characterization of chemical or biological liquids.…”
Section: Introductionmentioning
confidence: 99%